2000
DOI: 10.1002/1099-128x(200005/06)14:3<171::aid-cem591>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Application of PARAFAC for calibration with excitation-emission matrix fluorescence spectra of three classes of environmental pollutants

Abstract: Parallel factor analysis (PARAFAC) is applied to three calibrations of a field-portable, cuvette-based, singlemeasurement, excitation-emission matrix fluorometer. In the first example the fluorometer is calibrated based on interactions between a non-fluorescent DDT-type pesticide and a fluorescent dye. PARAFAC is employed to deconvolve the fluorescence profiles of dissociated and complexed dye states. Calibration is performed based on the intensity of dye-pesticide fluorescence. In the second example, weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…It was shown that tryptophan and tyrosine and also high molecular weight Maillard reaction polymers and polyphenolic compounds were important fluorophores. In an investigation of the interactions between a nonfluorescent DDT-type pesticide and a fluorescent dye, PARAFAC was employed to find the fluorescence profiles of complexed dye states [9]. Furthermore, the ability to quantify trace pesticides and polycyclic aromatic hydrocarbons by fluorescence spectroscopy and PARAFAC modeling was investigated by Jiji et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that tryptophan and tyrosine and also high molecular weight Maillard reaction polymers and polyphenolic compounds were important fluorophores. In an investigation of the interactions between a nonfluorescent DDT-type pesticide and a fluorescent dye, PARAFAC was employed to find the fluorescence profiles of complexed dye states [9]. Furthermore, the ability to quantify trace pesticides and polycyclic aromatic hydrocarbons by fluorescence spectroscopy and PARAFAC modeling was investigated by Jiji et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the fluorescent DOM fractions that are generally observed in surface water, and that provide water quality information, are protein-like -indicator of microbial activity and humiclike -indicator of terrestrial activity. Many studies have shown that fluorescence spectroscopy can characterize natural organic matter [2] and detect different types of aquatic pollutants, like sewage, petroleum products or pesticides [59][60][61][62][63][64]. But another possible application could be the understanding of the interaction between metals salts (like uranyl ion or its complexes) and DOM (or soil fulvic acids) [65] to be able to develop a method or a device to monitor and predict the transport of radioactive metals in aquatic systems.…”
Section: Link Between 3d Fluorescence Spectroscopy and Canonical Polymentioning
confidence: 99%
“…The observed value x ijk then corresponds to the intensity of sample i at emission wavelength j and excitation wavelength k. [112][113][114] The scores and loadings of the PARAFAC model are estimated by minimizing the objective function The PARAFAC model is often used to decompose fluorescence data into trilinear components according to the number of fluorophores (F) present in the samples.…”
Section: Multiway Analysismentioning
confidence: 99%